2020
DOI: 10.17569/tojqi.627310
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Peer Feedback in the Practicum: Qualitative and Quantitative Practices

Abstract: Professional development for teacher-trainees is commonly viewed as the relationship between a university supervisor, a school mentor and the trainee. The feedback provided by more experienced practitioners is thought to enhance professional development process. On the other hand, peer-feedback can also be used as a means to facilitate teaching practices of pre-service teachers. By receiving and providing feedback, the teacher candidates can also gain a better understanding of their own learning processes. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…For Darling-Hammond and Bransford (2005), learning and theories of learning need to be at the center of teacher education as the phenomenon of learning should be the primary purpose of any educational process. In line with this aim, the findings from this study also revealed that teaching practicum supported with collaborative reflection yielded positive effects on building positive learning environment and relationships with the students (Gröschner et al, 2018;Yüksel & Başaran, 2020). According to Gröschner et al (2018), the use of technology in teacher training during reflection part promotes the process of analysing and discussing the points related to teaching experience.…”
Section: Discussionsupporting
confidence: 69%
“…For Darling-Hammond and Bransford (2005), learning and theories of learning need to be at the center of teacher education as the phenomenon of learning should be the primary purpose of any educational process. In line with this aim, the findings from this study also revealed that teaching practicum supported with collaborative reflection yielded positive effects on building positive learning environment and relationships with the students (Gröschner et al, 2018;Yüksel & Başaran, 2020). According to Gröschner et al (2018), the use of technology in teacher training during reflection part promotes the process of analysing and discussing the points related to teaching experience.…”
Section: Discussionsupporting
confidence: 69%
“…Eisner (1979) states that the purpose of this model is to implicitly assess ongoing assessment activities through the perception and interpretation of meaning that is richly informed by theory, philosophy, and educational history. Yüksel (2010) views the purpose of assessment in this model as creating a natural approach to understanding phenomena in specific contexts. Furthermore, this assessment model introduces the use of various social sciences and practical wisdom born from experience and environment.…”
Section: The Purpose Of Assessment Using Connoisseurship Modelmentioning
confidence: 99%
“…Literature addressing issues in classroom observations have included the observer effect on the classroom (Keegan, 2014;Rees, 1997), the nature of data collection during the lesson (Bunton, Stimpson & Lopez-Real, 2002;Wajnryb, 1992), and differences in who conducts the observation (Yüksel, 2011). On giving feedback following the observation, research has investigated the timing of feedback after the lesson (Watson & Williams, 2004), the role of classroom data during the feedback (Walsh & Mann, 2015), the development of trust (Chamberlin, 2000), authority during the feedback conference (Louw et al, 2016), and the nature good feedback (Brandt, 2008).…”
Section: Supervisory Observations and Feedback On Teachingmentioning
confidence: 99%